Trends of breast tumour laterality and age-wise incidence rates in North Indian population - Kakkar, Vikas; Sharma, Rajiv; Singh, Karanvir; Randhawa, Anmol (International Surgery Journal, 2020)
Background: The breast is a paired organ. The two breasts share many of the risk factors known to contribute to the development of cancer genetics, environmental exposure, diet, and estrogen exposure, etc. By studying differences in the occurrence of breast cancer between the left and right breast, we can control for these common risk factors. Previous studies of breast cancer asymmetry have established that the laterality ratio is greater than 1.0 in women. Methods: We have taken 420 total cases to study the breast tumour laterality in women and age wise incidence of carcinoma breast in northern India. The study included all consecutive adult patients with histologically confirmed breast cancer, either invasive or carcinoma in situ. Multiple cancers were defined as two or more primary cancers occurring in an individual that were not an extension, recurrence, or metastasis. Based on the chronology of presentation, they were categorized as synchronous or metachronous primaries. Results: Out of 420 cases of breast cancer it was seen that 193 patients i.e. 45.95% of women under observation had left sided breast tumour, 225 patients i.e. 53.57% of women had right sided breast tumour and only 2 patients i.e. 0.48% patients had bilateral lesions in the breast. Conclusions: This result suggests the possible role of estrogen hormone in the reversed lateralization of breast cancer in comparison to other paired organ cancers in post-menopausal women suggesting that North Indian population has higher incidence of right sided breast cancer.